THE NARRATION OF DIGITAL LITERACY MOVEMENT IN INDONESIA - Mery Yanti; Yusnaini Yusnaini (Informasi, 2018)
This article aims to analyze the digital literacy movement in Indonesia and its determinant using the narrative approach. Empirical research is carried out with qualitative content analysis methods. The primary data of the study came from 255 online news which contained digital literacy keywords that were detected by Google search engines and published in trusted online media. Secondary data collected from publications of government, private, and civil society organizations related to digital literacy. We use an interactive model and Atlas.ti 8 to analyze research data. The results showed that each actor had a variety of views about the definitions and situations that underlie digital literacy problems. The digital literacy movement narrative in Indonesia can be explained using the logic of the problem - solution - results. Problem narratives tend to be based on data from a variety of data sources on the profile and behavior of internet users, the development of e-commerce, digital security and crime, digital radicalism, basic competencies of digital literacy, national competitiveness, and the online mass media industry. Starting from the problem narrative, the actors proposed the same solution, namely strengthening digital literacy of internet users, although they differed in identifying target groups. The goals of this solution are a reduction in digital crime, an increase in the digital economy, knowledge, digital skills, and digital governance, as well as the birth of practices in the use of information and communication technology that refers to three principles, namely: security principle, economic principles, and social-cultural principle. We identified four actors who acted as victims in the digital literacy movement narrative in Indonesia: society as a whole, religious institutions, state institutions, population, economic commodities, and market participants. The criminal's character includes internet users, legal players, government institutions, and politicians. Meanwhile, heroes are all actors acting in the digital literacy movement in Indonesia. Fours factors contributed to digital literacy movement: public participation, commitment and togetherness, shared goals and interests, and a massive, systematic, and synergistic strategy, movement management, and learning process. We discuss the theoretical and practical implications of these findings.NARASI GERAKAN LITERASI DIGITAL DI INDONESIAArtikel ini bertujuan menganalisis gerakan literasi digital di Indonesia dan determinannya dengan pendekatan naratif. Riset empiris dilaksanakan dengan metode analisis isi kualitatif. Data primer penelitian berasal dari 255 berita online yang mengandung kata kunci “literasi digital” yang di deteksi mesin pencari Google dan dipublikasikan di media online terpercaya. Data sekunder dikumpulkan dari publikasi organisasi pemerintah, swasta, dan/atau masyarakat sipil yang berhubungan dengan literasi digital. Analisis data penelitian menggunakan model interaktif dengan bantuan software Atlas.ti 8. Hasil penelitian menunjukkan setiap aktor memiliki keragaman pandangan tentang definisi dan situasi yang melatari masalah literasi digital. Alur cerita gerakan literasi digital di Indonesia bisa dijelaskan menggunakan logika masalah – solusi – hasil. Narasi masalah cenderung berbasis data dari beragam sumber data tentang profil dan perilaku pengguna internet, perkembangan e-commerce, keamanan dan kriminalitas digital, radikalisme digital, kompetensi dasar literasi digital, daya saing bangsa, dan industri media massa daring. Bertolak dari narasi masalah, para aktor mengusulkan solusi yang sama, yakni penguatan literasi digital pengguna internet, meski berbeda dalam identifikasi kelompok sasaran. Hasil akhir solusi ini adalah berkurangnya kriminalitas digital, meningkatnya perekonomian digital, pengetahuan, keterampilan digital, dan digital governance, serta melahirkan praktik-praktik penggunaan teknologi informasi dan komunikasi yang mengacu ke tiga prinsip, yakni: prinsip keamanan, prinsip ekonomi, dan prinsip sosio-kultural. Peneliti mengidentifikasi empat aktor yang berperan sebagai korban dalam narasi gerakan literasi digital di Indonesia, yakni: masyarakat secara keseluruhan, institusi agama, institusi negara, populasi penduduk, komoditas ekonomi, dan para pelaku pasar. Para penjahatnya meliputi pengguna internet, para pelaku pasar berbadan hukum, institusi pemerintah, dan oknum para politisi. Sedangkan, pahlawannya adalah semua aktor yang bertindak nyata dalam gerakan literasi digital di Indonesia. gerakan literasi digital dipengaruhi empat faktor yakni: partisipasi publik, komitmen dan kebersamaan, tujuan dan kepentingan bersama, dan strategi yang masif, sistematis, dan sinergis, manajemen gerakan, dan proses pembelajaran. Peneliti implikasi teoretis dan praktis temuan ini.